A Case of Diplomatic Symbiosis: France, Israel and the Former French Colonies in Africa, 1958–62. (January 2016) - Heimann, Gadi
This article deals with the interesting three-way relationship between Israel, France, and the former French colonies in Africa located south of the Sahara during the years 1958–62. The main argument of the paper is that in French Africa Israel and France maintained a sort of symbiosis: by seeking its own self-interest, each side fulfilled a vital function for the other. France showed great patience with Israel's attempts to penetrate its former colonies, more so than vis-a-vis any other countries. From Israel's standpoint this was a great opportunity, since it granted Israel a kind of exclusivity over supplementing French aid in its former colonies: France removed possible competition and made the assistance that Israel could offer even more attractive to the Africans. For its part, Israel saw itself as being required, almost without exception, to obtain France's consent of undertakings that it initiated in the African states. Therefore, if it was decreed that the new states in Africa were to receive assistance from other countries, then Israel was a convenient default, since it, more than any other country, showed sensitivity to the French interests there.